The Influence Of Pet Influencer @Kiwibritishcat On The Image Of The Metro Jaya Police Human Resources Bureau - Khalisa, Nadine Nur; Rachim, Widya Natassha; Kampf, Constance (LPPM Universitas PGRI Sumatera Barat, 2024)
In the rapidly developing world of public relations. The way to spread awareness of a brand is by doing endorsements. Endorsers who were previously actresses, athletes and public figures, have now been found